Implementation of a method to improve collaboration between stakeholders through the Kanban tool in construction projects - Linares Calle, Cielo Alejandra (2024)
Over time, construction projects have found it necessary to look for alternatives to improve collaboration between project stakeholders. To solve this problem, new technologies and Lean methodologies have been adopted. Therefore, this aims to implement a method to improve the management of collaboration between stakeholders during the execution stage of a construction project using the Kanban tool principles of Lean Manufacturing through Asana. Throughout the investigation, the implementation and viability of the method is evident in the plastering item of a public investment project of the National Superintendence of Customs and Tax Administration (SUNAT) of Peru. To achieve the objective, an intensive literature on collaborative management has been carried out. The viability of the method in the market market has been accepted in an expert judgment and indicators to measure collaboration were raised. Data was then collected through interviews and ongoing visits to the construction site. A focus group was also developed for continuous improvement of the method throughout the life of the project. A flowchart was proposed through which collaboration in the item mentioned before could be improved, this from start to finish had eleven executable days to be completed, through Asana and the collaborative management that this allows, errors were corrected and with it, complete the plastering itemin the established time. Finally, it can be said that the method is reliable to reduce the delays that exist due to poor collaboration between in the execution stage of construction projects.